Pengaturan Tentang Sanksi Yang Dapat Dijatuhkan Kepada Anak Peserta Didik Menurut Undang-Undang Nomor 14 Tahun 2005 Tentang Guru Dan Dosen - M.Septian Hidayatul Chandra; Elly Sudarti; Nys.Arfa (Jurnal Riset Multidisiplin Edukasi, 2025)
The purpose of this study is to determine and analyze the limits of sanctions and future legal policies regarding the provision of sanctions that can be given to students according to Law Number 14 of 2005 concerning Teachers and Lecturers. The formulation of the problems in this study are 1). How is the regulation of the limits of sanctions in Law Number 14 of 2005 concerning Teachers and Lecturers that can be given to student? and 2). How is the future legal policy regarding the provision of sanctions to students.? This research uses a normative juridical research method with a statute approach, case approach, and conceptual approach. The results of this study state that 1). Law Number 14 of 2005 concerning Teachers and Lecturers has not explicitly regulated the types, forms, and limits of sanctions that can be given to students, thus causing normative vagueness and concerns of a teacher in exercising his professional rights. 2).For this reason, future legal policies need to be directed at updating regulations that formulate the types of legal sanctions, fair and transparent sanctioning procedures, and legal protection for teachers so that they are not easily criminalized. Sanctions must be educative, humane, and proportional, with a conflict resolution mechanism through mediation before taking legal action. Thus, it is expected to create a balance of protection between children's rights and teachers' authority, so that the goals of national education can be realized in a fair, dignified and effective manner.